Change above the Glass Ceiling: Corporate Social Responsibility and Gender Diversity in Japanese Firms. (June 2018) - Mun, Eunmi; Jung, Jiwook
This article examines how local organizations respond to the global norm of corporate social responsibility (CSR), focusing on the case of workplace gender diversity in Japan. Though many global institutional investors have declared their commitment to CSR principles, whether and how their investments actually improve local practices has yet to be examined. We hypothesize that changes implemented by local firms in response to pressure from global institutional investors are shaped by political dynamics among competing professional groups in organizations. Through interviews with CSR managers and consultants in Japan, we find that CSR managers push for gender diversity only in the upper ranks of their organizations. This helps managers limit resistance from human resources managers, who want to maintain the traditional employment system, while still gaining support from investor relations managers, who support changes that are visible to investors. Our findings from panel data analysis further document this change above the glass ceiling. Analyzing more than 800 Japanese firms between 2001 and 2009, we show that both foreign investment and the within-firm influence of CSR and investor relations managers significantly increased the number of women on boards and in managerial positions but did not improve the lot of those in non-managerial or entry-level positions. Our study contributes to research on diffusion and organizational change by illuminating interprofessional politics in the local implementation of global norms.